2020
DOI: 10.33772/etnoreflika.v9i3.877
|View full text |Cite
|
Sign up to set email alerts
|

Waterfront Sebagai Modal Sosial Ekonomi Masyarakat Di Tepian Sungai Kapuas

Abstract: Tujuan dalam penelitian ini adalah untuk mengetahui dampak pembangunan Waterfront City sebagai modal sosial ekonomi dalam fenomena perubahan yang signifikan terhadap masyarakat, terutama masyarakat sekitaran tepian Sungai Kapuas. Adapun metode yang digunakan pada penelitian ini adalah metode deskriptif kualitatif dengan pendekatan studi fenomenologis. Hasil yang didapat pada penelitian ini adalah, upaya yang dilakukan untuk merespon kerja sama dan partisipasi adalah bentuk kemampuan adaptasi masyakarat sekitar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
4
0
3
Order By: Relevance
“…Waterfront development in the BKB River area can present a new space for the public, especially as a space for communication and community interaction. The area can provide aspects of comfort, cleanliness, and health for the community (Ramadhan et al 2020). The results of the research data show that the comfort aspect can be seen from the availability of supporting facilities such as chairs and a large area.…”
Section: Post-normalization Social Impactmentioning
confidence: 97%
“…Waterfront development in the BKB River area can present a new space for the public, especially as a space for communication and community interaction. The area can provide aspects of comfort, cleanliness, and health for the community (Ramadhan et al 2020). The results of the research data show that the comfort aspect can be seen from the availability of supporting facilities such as chairs and a large area.…”
Section: Post-normalization Social Impactmentioning
confidence: 97%
“…Subsequently, in Asia [39] it was confirmed that the sustainable development of coastal areas in major cities such as Shanghai was generally weak compared to Chong Ming District, and this was because the main focus was on economic and social aspects [40]. The development of waterfronts in Indonesia, such as in Manado [41] and the Kapuas River [42], was able to increase the business sector in coastal areas. However, it ended up causing various urban problems such as garbage, city drainage, slum areas, traffic congestion, and social problems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Semakin banyaknya pengunjung yang datang membuka peluang-peluang usaha baru bagi masyarakat sekitar yang mayoritas berada di tingkat ekonomi menengah kebawah. Sebagian besar masyarakat pesisir ini bekerja sebagai buruh kasar, pedagang, dan tidak sedikit pengangguran [1]. Dampak dari adanya Gertak ini menjadi hal positif yang perlu ditingkatkan, tidak hanya sekedar menghadirkan dan membuka peluang dari beragamnya potensi yang ada, tetapi juga bagaimana akhirnya setiap peluang dan hal positif tadi khusus pada sektor ekonomi dapat di pertahankan serta semakin di kembangkan.…”
Section: Pendahuluanunclassified